MULTIMEDIA APPLICATIONS ON MUSIC INFO SHEILA ON 7 WITH MS. VISUAL BASIC 6.0 - Dedy Ardyanto; Yuce Yuliani, Skom, MM (Jurnal Sistem Informasi, 2005)
In scientific writing, the writer tries to discuss about creating multimedia applications,how do we combine images, text, sound and animation into a computer device forprocessing and processed to become a form of information presented in an interestingand entertaining character.Multimedia applications on Sheila On 7 music group created by using MicrosoftVisual Basic 6.0 is obtained giving convenience to the users who want to learn moreabout the band Sheila On 7.